Multilayer structure lithium-rich manganese-based positive electrode material and preparation method and application thereof
By adopting a multi-layer structure design in the lithium-rich manganese-based cathode material and gradually reducing the Mn element content, the problem of oxygen release during the material's circulation process is solved, and high thermal stability, safety and energy density are improved.
Patent Information
- Application Number
- CN202411623852.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-24
AI Technical Summary
Lithium-rich manganese-based positive electrode materials have oxygen release problems during circulation, which reduces the thermal stability of the material and increases the risk of thermal runaway from the battery, while increasing the energy density will reduce safety.
A multi-layer structure of lithium-rich manganese-based cathode material is used. By gradually reducing the Mn element content in the cathode material sub-coating, from the inner layer with high Mn content to the outer layer with low Mn content, a gradient distribution of element concentration is formed to alleviate oxygen release. and improve thermal stability.
Under the premise of maintaining the discharge capacity without loss, the thermal stability of the lithium -rich manganese base is significantly improved, and the safety and energy density of the lithium -ion battery is improved.
Smart Images

Figure BDA0005134569700000111 
Figure HDA0005134569740000011 
Figure HDA0005134569740000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a multi-layer structured lithium-manganese-rich positive electrode material, a preparation method and application thereof. Background Art
[0002] As a chemical power source with high specific energy density, cyclic charge and discharge, and environmental friendliness, lithium-ion batteries have been widely used in 3C fields such as mobile phones and computers and have become one of the strong candidates for power sources for hybrid and pure electric vehicles. The energy density that can be achieved by common lithium-ion secondary batteries is <300Wh / kg, which cannot meet the requirements of the cruising range of pure electric vehicles. Therefore, the energy density of existing batteries needs to be greatly improved. However, increasing the energy density of batteries will reduce their safety and easily cause thermal runaway and explosion, which seriously limits the application of lithium-ion batteries in large-scale energy storage fields such as electric vehicles. In terms of energy density, high-energy-density lithium-ion batteries often require high-specific-energy positive and negative electrode materials. Therefore, in recent years, high-discharge specific-capacity positive electrode materials have attracted more and more attention. Among them, lithium-rich manganese-based positive electrode materials can simultaneously realize the participation of transition metal cations and lattice oxygen anions in redox reactions, so their discharge capacity is greater than 300mAh / g. However, compared with other positive electrode materials, lithium-rich manganese-based positive electrode materials have the problem of oxygen release during the cycle, which significantly reduces the thermal stability of the material and increases the risk of thermal runaway of the battery.
[0003] Alleviating oxygen release can fundamentally and thoroughly improve the thermal stability of lithium-rich manganese-based positive electrode materials. In recent years, many attempts have been made at home and abroad to dope, coat and other surface treatment methods on lithium-rich manganese-based positive electrode materials. However, the above modification methods inevitably sacrifice part of the discharge capacity and reduce the battery energy density. Summary of the invention
[0004] The purpose of the present invention is to provide a multilayer lithium-rich manganese-based positive electrode material, a preparation method and application thereof. The multilayer lithium-rich manganese-based positive electrode material in the present invention can alleviate oxygen release during charging while maintaining no loss in discharge capacity, thereby greatly improving thermal stability.
[0005] The present invention provides a multilayer structured lithium-rich manganese-based positive electrode material, comprising n positive electrode material sub-coatings, wherein the Mn element content in the first positive electrode material sub-coating to the nth positive electrode material sub-coating decreases successively;
[0006] Taking the total molar number of Mn, Co and Ni as 100%, the molar content of Mn element in the first positive electrode material sub-coating is 65-80%; the molar content of Mn element in the nth positive electrode material sub-coating is 25-55%; n is any integer between 2 and 6;
[0007] The first positive electrode material sub-coating layer is in contact with the positive electrode current collector.
[0008] Preferably, the thickness of the positive electrode material sub-coating layer is 10 to 40 μm.
[0009] Preferably, the n positive electrode material sub-coatings have the same thickness.
[0010] Preferably, taking the total molar number of Mn, Co and Ni as 100%, the total molar content of Mn element in the multilayer structure lithium-rich manganese-based positive electrode material is 50-70%.
[0011] Preferably, the multilayer structured lithium-rich manganese-based positive electrode material further comprises a single crystal nickel ternary positive electrode material layer, and the single crystal nickel ternary positive electrode material layer is in contact with the nth positive electrode material sub-coating layer;
[0012] The nickel ternary positive electrode material layer in the single crystal includes LiNi 0.33 Co 0.33 Mn 0.33 O2 and / or LiNi 0.5 Co 0.2 Mn 0.3 One or more of O2.
[0013] The present invention provides a method for preparing the multilayer structure lithium-rich manganese-based positive electrode material as described above, comprising the following steps:
[0014] A) mixing the first lithium-rich manganese-based positive electrode material, the second lithium-rich manganese-based positive electrode material, ... the nth lithium-rich manganese-based positive electrode material with a conductive agent, a binder and a solvent respectively to obtain a first positive electrode slurry, a second positive electrode slurry, ... the nth positive electrode slurry;
[0015] The Mn content in the first lithium-rich manganese-based positive electrode material, the second lithium-rich manganese-based positive electrode material, ... the nth lithium-rich manganese-based positive electrode material decreases in sequence; n is any integer between 2 and 6;
[0016] B) coating the first positive electrode slurry on the surface of the positive electrode current collector and drying it to form the first positive electrode material sub-coating layer, and then coating the second positive electrode slurry on the surface of the first positive electrode material sub-coating layer, and drying it to form the second positive electrode material sub-coating layer, and so on, until the nth positive electrode material sub-coating layer is obtained, thereby forming a multilayer structure of lithium-rich manganese-based positive electrode material.
[0017] Preferably, the mass fraction of the lithium-rich manganese-based positive electrode material in the first positive electrode slurry, the second positive electrode slurry, ... the nth positive electrode slurry is 95-96%.
[0018] The present invention provides a positive electrode, comprising a positive electrode current collector, wherein both sides of the positive electrode current collector are composited with positive electrode materials, and the positive electrode material is the multilayer structure lithium-manganese-rich positive electrode material described above.
[0019] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is the positive electrode described above.
[0020] The present invention provides an application of the multilayer structure lithium-rich manganese-based positive electrode material as described above in reducing gas generation during the charging and discharging process of the lithium-rich manganese-based positive electrode material.
[0021] The present invention provides a multilayer structure lithium-rich manganese-based positive electrode material, including n positive electrode material sub-coatings, wherein the Mn element content in the first positive electrode material sub-coating decreases successively to the nth positive electrode material sub-coating; the total molar number of Mn, Co and Ni is 100%, the molar content of the Mn element in the first positive electrode material sub-coating is 65-80%; the molar content of the Mn element in the nth positive electrode material sub-coating is 25-55%; n is any integer between 2 and 6; the first positive electrode material sub-coating is in contact with the positive electrode current collector. The present invention uses lithium-rich manganese-based positive electrode materials with different Mn contents to construct a multilayer structure distribution of lithium-rich manganese-based positive electrode materials with a high Mn content in the inner layer and a low Mn content in the outer layer, wherein the high Mn material component provides high capacity, and the low Mn component provides high thermal stability. By controlling the Mn element content to remain unchanged, regulating the spatial distribution of the Mn element can achieve high thermal stability, high safety and high specific energy lithium-ion batteries.
[0022] In addition, compared with modification methods such as doping and coating that can only be used for small-batch production, the method in the present invention is simple to operate and can be used for large-scale production, which is helpful for preparing high-energy density and high-safety lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0024] Figure 1 This is a schematic diagram of the structure of the multi-layer lithium-rich manganese-based positive electrode material of the present invention;
[0025] Figure 1 In the figure, 1 is a positive electrode current collector, 2 is a first positive electrode material sub-coating, 3 is a second positive electrode material sub-coating, 4 is a third positive electrode material sub-coating, and 5 is a nickel ternary positive electrode material layer in a single crystal;
[0026] Figure 2 The morphology and elemental analysis of the multi-layer structure lithium-rich manganese-based positive electrode sheet of Example 1 of the present invention;
[0027] Figure 3 This is the first cycle charge and discharge curve of the lithium ion battery of Example 1 of the present invention;
[0028] Figure 4 This is the first cycle charge and discharge curve of the lithium ion battery of Comparative Example 1 of the present invention;
[0029] Figure 5 This is the DSC curve of the positive electrode material of the lithium ion battery of Example 1 of the present invention;
[0030] Figure 6 This is the DSC curve of the positive electrode material of the lithium ion battery of Comparative Example 1 of the present invention;
[0031] Figure 7 This is the ARC test curve of the lithium-ion battery in Example 1 of the present invention;
[0032] Figure 8 This is the ARC test curve of the lithium-ion battery of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The present invention provides a multilayer structured lithium-rich manganese-based positive electrode material, comprising n positive electrode material sub-coatings, wherein the Mn element content in the first positive electrode material sub-coating to the nth positive electrode material sub-coating decreases successively;
[0034] Taking the total molar number of Mn, Co and Ni as 100%, the molar content of Mn element in the first positive electrode material sub-coating is 65-80%; the molar content of Mn element in the nth positive electrode material sub-coating is 25-55%; n is any integer between 2 and 6;
[0035] The first positive electrode material sub-coating layer is in contact with the positive electrode current collector.
[0036] In the present invention, the multilayer lithium-rich manganese-based positive electrode material has a stacked structure formed by n sub-coatings, where n is any integer between 2 and 6, more preferably any integer between 2 and 5, such as 2, 3, 4, 5, 6, preferably a range value with any of the above values as the upper or lower limit.
[0037] In the present invention, any sub-coating contains a lithium-rich manganese-based positive electrode material, that is, the first positive electrode material sub-coating includes the first lithium-rich manganese-based positive electrode material, the second positive electrode material sub-coating includes the second lithium-rich manganese-based positive electrode material, ... and so on, the nth positive electrode material sub-coating includes the nth lithium-rich manganese-based positive electrode material, and the n-layer structure formed by the n sub-coatings has the characteristic of element concentration gradient distribution. In the present invention, the element concentration gradient preferably refers to the Mn element having a concentration gradient distribution in the n-layer structure. Specifically, the Mn element content decreases from the first positive electrode material sub-coating to the nth positive electrode material sub-coating.
[0038] In the present invention, taking the total molar number of Mn, Co and Ni in each coating as 100%, the molar content of Mn element in the first positive electrode material sub-coating is preferably 65-80%, more preferably 65-75%, such as 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, preferably with any of the above values as the upper or lower limit of the range value; the nth positive electrode material sub-coating The molar content of Mn element is 25-55%, more preferably 30-50%, such as 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, preferably a range value with any of the above values as the upper or lower limit.
[0039] In the present invention, the thickness of the n sub-coatings is controlled between 10 and 40 μm, preferably 15 to 30 μm. The thickness of any two sub-coatings may be the same or different. Preferably, in an embodiment of the present invention, the coating thickness of the sub-coatings is the same.
[0040] The multilayer structure lithium-rich manganese-based positive electrode material of the present invention preferably also includes a single crystal nickel ternary positive electrode material layer, wherein the single crystal nickel ternary positive electrode material layer is in contact with the nth positive electrode material sub-coating layer; the single crystal nickel ternary positive electrode material layer includes NCM111 (LiNi 0.33 Co 0.33 Mn 0.33 O2) and NCM523(LiNi 0.5 Co 0.2 Mn 0.3 O2) one or two; the content of Mn element in the nickel ternary positive electrode material layer in the single crystal is preferably lower than the content of Mn element in the nth positive electrode material sub-coating.
[0041] In the present invention, taking the total molar number of Mn, Co and Ni in the multilayer lithium-rich manganese-based positive electrode material as 100%, the total molar content of the Mn element is preferably 50-70%, more preferably 55-65%, such as 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, preferably a range value with any of the above values as the upper or lower limit.
[0042] The present invention also provides a method for preparing the multilayer structure lithium-rich manganese-based positive electrode material as described above, comprising the following steps:
[0043] A) mixing the first lithium-rich manganese-based positive electrode material, the second lithium-rich manganese-based positive electrode material, ... the nth lithium-rich manganese-based positive electrode material with a conductive agent, a binder and a solvent respectively to obtain a first positive electrode slurry, a second positive electrode slurry, ... the nth positive electrode slurry;
[0044] The Mn content of the first lithium-rich manganese-based positive electrode material, the second lithium-rich manganese-based positive electrode material, ... the nth lithium-rich manganese-based positive electrode material decreases in sequence; n is any integer between 2 and 20;
[0045] B) coating the first positive electrode slurry on the surface of the positive electrode current collector and drying it to form the first positive electrode material sub-coating layer, and then coating the second positive electrode slurry on the surface of the first positive electrode material sub-coating layer, and drying it to form the second positive electrode material sub-coating layer, and so on, until the nth positive electrode material sub-coating layer is obtained, thereby forming a multilayer structure of lithium-rich manganese-based positive electrode material.
[0046] In the present invention, the n kinds of lithium-rich manganese-based positive electrode materials with different manganese contents can be selected with reference to the contents of Mn, Ni, Co and Li elements in the n positive electrode material sub-coatings described above, and the present invention will not be repeated here.
[0047] In the present invention, the conductive agent preferably includes carbon nanotubes and / or conductive carbon black, more preferably a mixture of carbon nanotubes and conductive carbon black in a mass ratio of 1: (1-5), and most preferably a mixture of carbon nanotubes and conductive carbon black in a mass ratio of 1: (3-4). Specifically, in an embodiment of the present invention, it is preferred that the conductive agent is mixed with a solvent to form a conductive paste for use, and more preferably, the conductive agent, a dispersant and a solvent are mixed to form a conductive paste for use, the dispersant is preferably polyvinyl pyrrolidone, the mass fraction of the conductive agent in the conductive paste is preferably 1-15%, more preferably 1-10%, the mass fraction of the dispersant in the conductive paste is preferably 5-15%, more preferably 10-12%.
[0048] In the present invention, the binder is preferably polyvinylidene fluoride.
[0049] In the present invention, in the first positive electrode slurry, the second positive electrode slurry, ... the nth positive electrode slurry, the mass fraction of the lithium-rich manganese-based positive electrode material is preferably 95-96%, the mass fraction of the conductive slurry is preferably 3.5-4%, and the mass fraction of the binder is preferably 1-1.5%. The amounts of the lithium-rich manganese-based positive electrode material, the conductive slurry and the binder in the first positive electrode slurry, the second positive electrode slurry, ... the nth positive electrode slurry may be the same or different. The present invention preferably sets the amounts of the lithium-rich manganese-based positive electrode material, the conductive slurry and the binder in the n kinds of positive electrode slurries to be the same, so that the change trend of each element (Mn, Ni, Co and Li) in the n kinds of slurries applied sequentially is the same as the change trend of each element (Mn, Ni, Co and Li) in the n kinds of lithium-rich manganese-based positive electrode materials contained in the n kinds of slurries, which is convenient for production operation.
[0050] In the present invention, when the contents of lithium-rich manganese-based materials in the first positive electrode slurry, the second positive electrode slurry, ... to the nth positive electrode slurry are the same, the above-mentioned "the Mn element content decreases from the first positive electrode material sub-coating to the nth positive electrode material sub-coating" of the present invention can be equivalent to "the Mn element content decreases from the first lithium-rich manganese-based positive electrode material to the nth lithium-rich manganese-based positive electrode material", and the above conclusion is also valid for Li, Ni and Co elements, and the present invention will not repeat them here.
[0051] In the present invention, the first lithium-rich manganese-based positive electrode material can be only one lithium-rich manganese-based positive electrode material, or two or more lithium-rich manganese-based positive electrode materials can be mixed and used. Similarly, the second lithium-rich manganese-based positive electrode material, ... the nth lithium-rich manganese-based positive electrode material can all be one lithium-rich manganese-based positive electrode material or a mixture of several lithium-rich manganese-based positive electrode materials, as long as the final stoichiometric ratio of each element meets the requirements of the element concentration gradient change.
[0052] The present invention preferably coats and dries the first positive electrode slurry on one surface of the positive electrode current collector, and then coats and dries the first positive electrode slurry on the other surface of the positive electrode current collector to obtain a double-sided coated first positive electrode material sub-coating, and then coats the second positive electrode slurry on the surface of the first positive electrode material sub-coating on both sides, and forms a second positive electrode material sub-coating after drying, and so on, until the nth positive electrode material sub-coating is obtained to form a multi-layer structure lithium-manganese-rich positive electrode material.
[0053] The present invention also provides a positive electrode, which includes a positive electrode collector and a positive electrode material double-sidedly composited on the surface of the positive electrode collector, wherein the positive electrode material is the multi-layer structure lithium-manganese-rich positive electrode material described above.
[0054] According to the preparation method of the multilayer structure lithium-rich manganese-based positive electrode material, the present invention performs double-sided coating on the surface of the positive electrode current collector to obtain a positive electrode sheet, and then rolls and slices the positive electrode sheet for standby use.
[0055] In the present invention, the positive electrode current collector may be a positive electrode current collector commonly used in the art, such as aluminum foil.
[0056] The present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is preferably the positive electrode described above.
[0057] In the present invention, the negative electrode is preferably metallic lithium. The present invention has no special restrictions on the types of the separator and the electrolyte, and the separator and the electrolyte commonly used in the art can be used.
[0058] The present invention assembles positive and negative electrode sheets into a battery core by laminating them, and injects electrolyte into the battery core after baking to obtain a lithium ion battery.
[0059] The present invention also provides an application of the multilayer structure lithium-rich manganese-based positive electrode material described above in reducing the gas generation of the lithium-rich manganese-based positive electrode material during the charging and discharging process. The present invention uses a multilayer structure lithium-rich manganese-based positive electrode material with a reduced Mn element concentration gradient as the positive electrode material. The low-Mn content coating in contact with the electrolyte provides high thermal stability, and the high-Mn content coating in contact with the positive electrode current collector provides high discharge capacity, which can significantly reduce the gas generation phenomenon unique to the lithium-rich manganese-based positive electrode material during the cycle, thereby simultaneously improving the energy density and safety of the lithium-ion battery.
[0060] In addition, the method of the present invention is simple to operate, can be used for large-scale production, and is helpful for preparing high-energy-density and high-safety lithium-ion batteries.
[0061] In order to further illustrate the present invention, a multilayer lithium-manganese-rich positive electrode material, a preparation method and an application thereof provided by the present invention are described in detail below in combination with embodiments, but it should not be construed as limiting the scope of protection of the present invention.
[0062] Example 1
[0063] a) Li-rich manganese-based positive electrode materials with different Mn contents in the present invention 1.14 Ni 0.13 Co 0.13 Mn 0.52 O2(LR-NCM114), Li 1.08 Ni 0.25 Co 0.25 Mn 0.5 O2 (LR-NCM112) is from Ningbo Fuli Battery Material Technology Co., Ltd.;
[0064] b) mixing 1% by mass of carbon nanotubes, 3% by mass of conductive carbon black and 10% by mass of dispersant polyvinyl pyrrolidone with solvent N-methylpyrrolidone (NMP) and ultrasonically dispersing them to obtain a mixed conductive slurry;
[0065] c) adding a lithium-rich manganese-based positive electrode material, a conductive slurry, a polyvinylidene fluoride (PVDF) solution binder and an NMP solvent into a batching kettle and stirring to obtain lithium-ion battery positive electrode material slurries LR-NCM114-1 and R-NCM112-1, respectively, wherein the mass fraction of the lithium-rich manganese-based positive electrode material in the slurry is 95%, the mass fraction of the conductive slurry is 3.5%, and the mass fraction of the polyvinylidene fluoride is 1.5%.
[0066] d) coating the positive electrode material slurry LR-NCM114-1 on the positive electrode current collector, and after drying the electrode sheet, uniformly coating the positive electrode material slurry LR-NCM112-1 on both sides of the dried positive electrode material slurry LR-NCM114-1, and obtaining a multi-layer structure lithium-rich manganese-based positive electrode material electrode sheet after drying; wherein the thickness of the LR-NCM114-1 layer is 30 μm; the thickness of the LR-NCM112-1 layer is 30 μm;
[0067] e) rolling and slicing the positive electrode material sheet for later use. The obtained positive electrode sheet is denoted as P1, with a size of 72 mm*62 mm and a single-sided surface density of 16 mg / cm 2 ;
[0068] f) Using 100um thick lithium foil as the negative electrode, denoted as N, where the negative electrode sheet size is 75mm*64mm;
[0069] h) assembling the positive and negative electrode sheets into a battery cell by laminating, wherein the number of positive electrode layers is 10;
[0070] i) The battery cell is baked and injected with electrolyte to obtain a lithium-ion battery.
[0071] The morphology and element analysis of the positive electrode sheet obtained in Example 1 are as follows: Figure 2 As shown by Figure 2 It can be seen that the Mn content in the outer layer (LR-NCM112-1) accounts for 52.8%, the Co content accounts for 23.5%, and the Ni content accounts for 23.7%; the Mn content in the inner layer (LR-NCM114-1) accounts for 66.8%, the Co content accounts for 16.6%, and the Ni content accounts for 16.6%.
[0072] Example 2
[0073] A lithium-ion battery was prepared according to the preparation process of Example 1, except that the Li1.14 Ni 0.13 Co 0.13 Mn 0.52 O2(LR-NCM114) replaced by Li 1.17 Ni 0.1 Co 0.1 Mn 0.6 O2(LR-NCM116), and the obtained positive electrode is denoted as P2.
[0074] Example 3
[0075] A lithium-ion battery was prepared according to the preparation process of Example 1, except that the Li 1.14 Ni 0.13 Co 0.13 Mn 0.52 O2(LR-NCM114), Li 1.08 Ni 0.25 Co 0.25 Mn 0.5 O2(LR-NCM112) replaced by Li 1.14 Ni 0.13 Co 0.13 Mn 0.52 O2(LR-NCM114), Li 1.08 Ni 0.25 Co 0.25 Mn 0.5 O2(LR-NCM112) and Li 1.12 Ni 0.16 Co 0.16 Mn 0.48 O2 (LR-NCM113) and three kinds of lithium-rich manganese-based positive electrode materials with different Mn contents are coated in the order of LR-NCM114, LR-NCM113, and LR-NCM112, and the thickness of the three layers is 20μm; the obtained positive electrode is recorded as P3.
[0076] Example 4
[0077] A lithium-ion battery was prepared according to the preparation process of Example 1, except that the Li 1.14 Ni 0.13 Co 0.13 Mn 0.52 O2(LR-NCM114), Li 1.08 Ni 0.25 Co 0.25 Mn 0.5 O2(LR-NCM112) replaced by Li 1.17 Ni 0.1 Co 0.1 Mn 0.6O2(LR-NCM116), Li 1.14 Ni 0.13 Co 0.13 Mn 0.52 O2(LR-NCM114), Li 1.08 Ni 0.25 Co 0.25 Mn 0.5 O2(LR-NCM112), Li 1.12 Ni 0.16 Co 0.16 Mn 0.48 O2 (LR-NCM113) and four lithium-rich manganese-based positive electrode materials with different Mn contents are coated in the order of LR-NCM116, LR-NCM114, LR-NCM113, and LR-NCM112, and the thickness of the four layers is 15μm; the obtained positive electrode is recorded as P4.
[0078] Example 5
[0079] A lithium-ion battery was prepared according to the preparation process of Example 1, except that the Li 1.14 Ni 0.13 Co 0.13 Mn 0.52 O2(LR-NCM114), Li 1.08 Ni 0.25 Co 0.25 Mn 0.5 O2(LR-NCM112) replaced by Li 1.17 Ni 0.1 Co 0.1 Mn 0.6 O2(LR-NCM116), Li 1.14 Ni 0.13 Co 0.13 Mn 0.52 O2(LR-NCM114), Li 1.12 Ni 0.16 Co 0.16 Mn 0.48 O2(LR-NCM113), Li 1.08 Ni 0.25 Co 0.25 Mn 0.5 O2 (LR-NCM112) four kinds of lithium-rich manganese-based positive electrode materials with Mn content, in addition, single crystal nickel ternary positive electrode material LiNi 0.33 Co 0.33 Mn 0.33O2 (NCM111), and the coating was carried out in the order of LR-NCM116, LR-NCM114, LR-NCM113, LR-NCM112, and NCM111, and the thickness of the five layers was 12 μm; the obtained positive electrode was recorded as P5.
[0080] Comparative Example 1
[0081] a) Li-rich manganese-based positive electrode material Li in the comparative example 1.12 Ni 0.16 Co 0.16 Mn 0.48 O2 (LR-NCM113) is from Ningbo Fuli Battery Material Technology Co., Ltd.;
[0082] b) adding 1% by mass of carbon nanotubes, 3% by mass of conductive carbon black and 10% by mass of dispersant polyvinyl pyrrolidone into solvent N-methyl pyrrolidone, mixing and ultrasonically dispersing to obtain a mixed conductive slurry;
[0083] c) adding a lithium-rich manganese-based positive electrode material, a conductive slurry, a polyvinylidene fluoride (PVDF) solution binder and an NMP solvent into a batching kettle, and stirring to obtain a lithium-ion battery positive electrode material slurry LR-NCM113-1, wherein the mass fraction of the lithium-rich manganese-based positive electrode material in the slurry is 95%, the mass fraction of the conductive slurry is 3.5%, and the mass fraction of the polyvinylidene fluoride is 1.5%;
[0084] d) coating the positive electrode material slurry LR-NCM113-1 on the positive electrode current collector, and after drying the electrode sheet, uniformly coating the electrode sheet on the other side of the current collector in the same manner, and obtaining a multi-layer structure lithium-rich manganese-based positive electrode material electrode sheet after drying, wherein the thickness of LR-NCM113-1 is 60 μm;
[0085] e) rolling and slicing the positive electrode material sheet for standby use. The obtained positive electrode sheet is denoted as P5, with a size of 72 mm*62 mm and a single-sided surface density of 16 mg / cm 2 ;
[0086] f) Using 100um thick lithium foil as the negative electrode, denoted as N, where the negative electrode sheet size is 75mm*64mm;
[0087] h) assembling the positive and negative electrode sheets into a battery cell by laminating, wherein the number of positive electrode layers is 10;
[0088] i) The battery cell is baked and injected with electrolyte to obtain a lithium-ion battery.
[0089] Figure 3 is the first cycle charge and discharge curve of the lithium ion battery in Example 1, Figure 4 The first cycle charge and discharge curve of the lithium-ion battery in comparative example 1 is shown in FIG. Figure 3 and Figure 4 It can be seen that compared with Example 1, the comparative example can achieve the normal performance of the gram capacity of the positive electrode material and achieve the same battery energy density of the whole battery, but the 50-cycle capacity retention rate of the battery in Example 1 is 85.3%, which is significantly better than 68.3% of the comparative example, and its thermal runaway temperature is 204.8°C, which is 4.8°C higher than that of the comparative example 1, but its calorific value is 765 J g -1 Only 1365 J g of Comparative Example 1 -1 That is, the method of the present invention can improve the cycle performance of the battery while ensuring the battery energy density and further optimize the safety performance of the battery.
[0090] Comparative Example 2
[0091] A lithium-ion battery was prepared according to the preparation process of Comparative Example 1, except that Li 1.12 Ni 0.16 Co 0.16 Mn 0.48 O2(LR-NCM113) replaced by Li 1.14 Ni 0.13 Co 0.13 Mn 0.52 O2 (LR-NCM114) lithium-rich manganese-based positive electrode material, the obtained positive electrode is denoted as P6.
[0092] The performance of the batteries obtained in Examples 1 to 5 and Comparative Examples 1 to 2 was tested:
[0093] Initial charge and discharge experiment: The lithium-ion battery was placed at room temperature (25°C) for 36 hours, and charged and discharged at room temperature with a 0.1C constant current (400mA), with a cut-off voltage of 2-4.8V, and the discharge capacity of the first cycle was recorded. The first cycle charge and discharge curves of the lithium-ion batteries in Example 1 and Comparative Example 1 are shown in Figure 1. Figure 3 and Figure 4 shown.
[0094] Thermal stability test experiment: After the lithium-ion battery is charged to 4.8V using a 0.1C constant current, the lithium-ion battery is disassembled in a glove box, the positive electrode sheet is taken out and the positive electrode material is gently scraped out. In the glove box, the charged positive electrode material powder and the electrolyte are added to a stainless steel high-pressure crucible in a mass ratio of 1:1 for differential scanning calorimetry (DSC). The DSC curves of the lithium-ion battery positive electrode materials in Example 1 and Comparative Example 1 are shown in Figure 1. Figure 5 and Figure 6 Show.
[0095] Safety test experiment: After the lithium-ion battery is charged to 4.8V using a 0.1C constant current, the lithium-ion battery is subjected to an accelerated calorimetry (ARC) test. During the test, the starting temperature is 30°C, the heating rate is 0.02°C / min, and the waiting time is 40min. The ARC test curves of the lithium-ion batteries in Example 1 and Comparative Example 1 are shown in FIG. Figure 7 and Figure 8 Show.
[0096] The test results are shown in Table 1:
[0097] Table 1 Performance comparison between the examples and the comparative examples
[0098]
[0099] The morphology and elemental analysis of Example 1 of the present invention are as follows Figure 2 As shown in the figure, it can be found that the multilayer structured lithium-rich manganese-based positive electrode sheet contains two Mn-rich lithium-rich manganese-based positive electrode materials, wherein the high Mn content component (LR-NCM114) is near one end of the current collector, and the low Mn content component (LR-NCM112) is on the outside away from the current collector. Example 1 and Comparative Example 1 were assembled into a battery and charged and discharged with a 0.1C constant current (400mA), with a cut-off voltage of 2-4.8V. It can be seen that the discharge capacity of Example 1 is 259.7mAh g -1 ( Figure 3 ), the discharge capacity of comparative example 1 is 251.6 mAh g -1 ( Figure 4 ), indicating that the multilayer structure of lithium-rich manganese-based positive electrode can achieve higher discharge capacity. By performing DSC tests on the 4.8V charged state materials of Example 1 and Comparative Example 1, it can be found that the heat release of Example 1 is 765.44 J g -1 ( Figure 5 ), the heat release of comparative example 1 is 1365.36 Jg -1 ( Figure 6 ), and at the same time, the lithium-ion batteries of Example 1 and Comparative Example 1 were subjected to ARC tests, and the results showed that the thermal runaway temperature of Example 1 was 204.82°C, and the thermal runaway temperature of Comparative Example 1 was 200.03°C. The above analysis shows that the multi-layer structure of lithium-rich manganese-based positive electrode sheets can achieve higher discharge capacity and higher thermal stability, and the multi-layer structure of positive electrode sheets is conducive to achieving high safety and high specific energy lithium-ion batteries.
[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A multilayer structured lithium-rich manganese-based positive electrode material, comprising n positive electrode material sub-coatings, wherein the Mn content in the first positive electrode material sub-coating to the nth positive electrode material sub-coating decreases successively; Taking the total molar number of Mn, Co and Ni as 100%, the molar content of Mn element in the first positive electrode material sub-coating is 65-80%; the molar content of Mn element in the nth positive electrode material sub-coating is 25-55%; n is any integer between 2 and 6; The first positive electrode material sub-coating layer is in contact with the positive electrode current collector.
2. The multilayer structured lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The thickness of the positive electrode material sub-coating layer is 10-40 μm.
3. The multilayer structured lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The n positive electrode material sub-coating layers have the same thickness.
4. The multilayer structured lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: Taking the total molar number of Mn, Co and Ni as 100%, the total molar content of Mn element in the multilayer structure lithium-rich manganese-based positive electrode material is 50-70%.
5. The multi-layer structured lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The multi-layer structured lithium-rich manganese-based positive electrode material further includes a single crystal nickel ternary positive electrode material layer, and the single crystal nickel ternary positive electrode material layer is in contact with the nth positive electrode material sub-coating layer; The nickel ternary positive electrode material layer in the single crystal includes LiNi 0.33 Co 0.33 Mn 0.33 O2 and / or LiNi 0.5 Co 0.2 Mn 0.3 One or more of O2.
6. The method for preparing the multilayer structured lithium-rich manganese-based positive electrode material according to claim 1, comprising the following steps: A) mixing the first lithium-rich manganese-based positive electrode material, the second lithium-rich manganese-based positive electrode material, ... the nth lithium-rich manganese-based positive electrode material with a conductive agent, a binder and a solvent respectively to obtain a first positive electrode slurry, a second positive electrode slurry, ... the nth positive electrode slurry; The Mn content in the first lithium-rich manganese-based positive electrode material, the second lithium-rich manganese-based positive electrode material, ... the nth lithium-rich manganese-based positive electrode material decreases in sequence; n is any integer between 2 and 6; B) coating the first positive electrode slurry on the surface of the positive electrode current collector and drying it to form the first positive electrode material sub-coating layer, and then coating the second positive electrode slurry on the surface of the first positive electrode material sub-coating layer, and drying it to form the second positive electrode material sub-coating layer, and so on, until the nth positive electrode material sub-coating layer is obtained, thereby forming a multilayer structure of lithium-rich manganese-based positive electrode material.
7. The preparation method according to claim 6, characterized in that: The mass fraction of the lithium-rich manganese-based positive electrode material in the first positive electrode slurry, the second positive electrode slurry, ... the nth positive electrode slurry is 95-96%.
8. A positive electrode, comprising a positive electrode current collector, wherein both sides of the positive electrode current collector are composited with positive electrode materials, and the positive electrode material is the multilayer structure lithium-rich manganese-based positive electrode material according to any one of claims 1 to 5 or the multilayer structure lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 6 to 7.
9. A lithium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode is the positive electrode according to claim 8.
10. Use of the multilayer structure lithium-rich manganese-based positive electrode material according to any one of claims 1 to 5 in reducing gas generation during charging and discharging of the lithium-rich manganese-based positive electrode material.